2018
DOI: 10.3390/su10020276
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Bioretention Construction Details to Local Practices in Finland

Abstract: Bioretention is a method of storm water management that includes several processes following the natural hydrological cycle. Bioretention, or variations of it, include rain gardens and bioswales, infiltrates, filtrates, evapotranspirates, and help to store and manage storm water run-off. A bioretention cell retains water, removes pollutants, and provides water elements for urban green areas. Although bioretention is a promising method for multifunctional storm water management, its construction details should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The effects of the additional exogenous carbon to drive denitrification could be clearly seen in BCs with the removal of nitrate (NO 3 − ) in module (c) with C showing significant (p < 0.05) enhancement (85%, 87% and 94%) at all three HRTs, respectively, compared to the removal efficiency by module (d) without C (74%, 76% and 82% at three HRTs, respectively) ( Figure 2A). The fact that the addition of carbon source as electro donor can facilitate denitrification and improve NO 3 − removal in bioretention system has also been reported by other studies [38,54]. The results also indicated that the removal of NO 3 − in module (c) with shallow SZ (200 mm) showed significant (p < 0.05) enhancement (85%, 87% and 94% at three HRTs, respectively) compared to those in the module (b) with deep SZ (300 mm) (71%, 73% and 86% at three HRTs, respectively).…”
Section: Nitrogen Removalsupporting
confidence: 68%
See 2 more Smart Citations
“…The effects of the additional exogenous carbon to drive denitrification could be clearly seen in BCs with the removal of nitrate (NO 3 − ) in module (c) with C showing significant (p < 0.05) enhancement (85%, 87% and 94%) at all three HRTs, respectively, compared to the removal efficiency by module (d) without C (74%, 76% and 82% at three HRTs, respectively) ( Figure 2A). The fact that the addition of carbon source as electro donor can facilitate denitrification and improve NO 3 − removal in bioretention system has also been reported by other studies [38,54]. The results also indicated that the removal of NO 3 − in module (c) with shallow SZ (200 mm) showed significant (p < 0.05) enhancement (85%, 87% and 94% at three HRTs, respectively) compared to those in the module (b) with deep SZ (300 mm) (71%, 73% and 86% at three HRTs, respectively).…”
Section: Nitrogen Removalsupporting
confidence: 68%
“…In addition, to date, little information on the impact of the depth of SZ on contaminant removal in BCs is available. Also, there is relatively limited data available on water quality improvement (e.g., as a function of hydraulic residence time (HRT) and detailed pollutant fate in retrofited BCs with the saturated zone) [35,36].Actually, BCs have been adopted by many urban catchments worldwide to reduce storm flows and improve runoff quality [37,38]. In recent years, integrating the LID practices with the urban catchment for the sustainability of urban hydrology under the Sponge City Programme has been strongly implemented in China [39].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The upper part of the filter material layer was covered with 50 mm planting soil. The construction details of the system are supposed to adapt to local environmental conditions [22], and Photinia fraseri were planted in the unit, which is a commonly available plant species (Hefei, China) with a planting density of 15 units per square meter. At the bottom of each unit, perforated water collection pipes with 75 mm diameter were arranged, and a perforated collector outlet was located at the original rain water storage tank located in the park.…”
Section: Experimental Sitementioning
confidence: 99%
“…Multiple plant-related mechanisms, such as phytoextraction and phytodegradation [27], are important for biological treatment and pollutant removal. Again, different SUDS have different impacts; i.e., bioretention cells are effective in filtration, sedimentation, adsorption, and plant uptake [28], while extensive green roofs have a varying ability to retain pollutants depending on the season, substrate type, event size, and rainfall regime [29,30]. If the functions of different SUDS are known, it is possible to match the right SUDS elements to meet local stormwater quality management needs in the design process.…”
Section: Multifunctional Sudsmentioning
confidence: 99%